Sociodemographic and Clinical Features of Children Dragged To Crime in Sivas Province - Sarı, Seda Aybüke; Çiçek, Ayla Uzun; Bütün, Celal; Yıldırım, Ali (The Bulletin of Legal Medicine, 2019)
Objective: In this study, it was aimed to investigate the sociodemographic characteristics, types of crime and intelligence levels of delinquent children and to determine the reasons that push these children into crime. Materials and Methods: The data of 86 cases who were referred to Cumhuriyet University pediatric and adolescent mental health and diseases outpatient clinic for forensic report by the judicial authorities between 01.01.2017-01.06.2018 were analyzed retrospectively. Age, gender, socioeconomic status, educational level, intelligence level and psychological diagnoses of children according to DSM-5; also, the characteristics of the crime and the results of the forensic reports were evaluated. Results: 90.6% of the cases were male. The mean age at the time of the crime was 13.76 ± 0.89. Most of them were children of low- and middle-level families with low socioeconomic status. 72% of the cases did not have any mental illness. Conduct Disorder (CD) was the most common mental disorder. The majority of cases (82.5%) had normal intelligence. The most frequently committed crime was “theft” (50%). 30.2% of the cases had a history of recurrent crime. Only 25.5% of these cases had the ability to perceive the legal meaning and results of the act and to direct their behavior. Conclusion: Juvenile delinquency is an increasing problem in our country. For this reason, it is important to determine the risk factors that lead children to commit crimes and to take necessary measures in this regard.